1981
DOI: 10.1002/pd.1970010304
|View full text |Cite
|
Sign up to set email alerts
|

Technical and theoretical considerations in the HLA typing of amniotic fluid cells for prenatal diagnosis and paternity testing

Abstract: HLA typing of amniotic fluid cells has been used for the prenatal diagnosis of the HLA linked diseases congenital adrenal hyperplasia (21-OH-deficiency (21-OH-def) type) and complement C4 deficiency and it has also been used for the prenatal determination of paternity. There are, however, technical difficulties in this test associated with the weak expression of some B locus antigens on amniotic fluid cells, and theoretical difficulties related to associations between particular HLA antigens and the 21-OH-def … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The results of absorption experiments (table IV) indicated a lack of correlation between B17 antigen concentra tion on lymphocytes and Bgb expression on red blood cells. This is not surprising in view of other data indicating a lack of correlation between lymphocyte HLA antigen expres sion and HLA antigen expression on plate lets [4,5], or cultured cells [11,12], which in some cases may completely fail to express certain of the donor's particular HLA anti gens. Nordhagen [9] has also made a similar observation for Bga and Bgc expression.…”
Section: Discussionmentioning
confidence: 52%
“…The results of absorption experiments (table IV) indicated a lack of correlation between B17 antigen concentra tion on lymphocytes and Bgb expression on red blood cells. This is not surprising in view of other data indicating a lack of correlation between lymphocyte HLA antigen expres sion and HLA antigen expression on plate lets [4,5], or cultured cells [11,12], which in some cases may completely fail to express certain of the donor's particular HLA anti gens. Nordhagen [9] has also made a similar observation for Bga and Bgc expression.…”
Section: Discussionmentioning
confidence: 52%
“…This investigation would have been particularly useful as it has been shown that technical problems associated with the HLA typing of amniotic fluid cell cultures can lead to errors of interpretation. Pollack et al (1981) demonstrated that certain B locus antigens may be weakly expressed by these cells; this particularly applies to Bw44 (12), B7, B8, B13 and Bw48. Both B7 and B12 are present in this family, but we had no difficulty demonstrating B7 on the fetal cells.…”
Section: Resultsmentioning
confidence: 97%
“…The close linkage of the gene for CAH with the HLA complex has permitted not only the identification of heterozygous carriers within affected families (e.g., Dupont et al, 1977;Grosse-Wilde et d., 1979;Stuckey et al, 1980) but also the prenatal diagnosis of CAH via HLA-A,B,C typing of cultured amniotic fluid cells (AFC) derived from a fetus at risk (e.g., Couillin et al, 1979;Pollack et al, 1979;Forest er al., 1981). Recognition of haplotypes and therefore accurate prenatal diagnosis, however, may sometimes be difficult due to poor expression of certain HLA-A,B,C antigens on AFC or to HLA homozygosity (Pollack et al, 1981). Concomitant typing for HLA-DR on AFC as an additional marker, as we suggested in 1984 (Kreeb et al, 1984), could obviate some of these difficulties.…”
Section: Introductionmentioning
confidence: 81%